Enhancing sustainability in manufacturing processes: A comprehensive study on sustainability index and assessment methods in a Malaysia electronic industry - Khairil Izhan, Anuar; Amiril Sahab, Abdul Sani (Springer, 2025)
This paper addresses the challenges in balancing environmental, economic, and societal concerns in Malaysia’s electronic industry by proposing an integrated sustainability assessment method. The method combines quantitative and qualitative indicators, weighted for relevance to the industry, to create a unit-less sustainability index. Using real data from Malaysian electronic manufacturing companies, the index highlights strengths and weaknesses in sustainability performance across environmental, economic, and societal dimensions. The findings reveal opportunities for improvement, such as reducing emissions, mitigating wastewater pollution, and enhancing working conditions, providing actionable insights for decision-makers to drive sustainable practices.